Stimulation Mapping Using Stereoelectroencephalography: Current and Future Directions - George, Derek D.; Ojemann, Steven G.; Drees, Cornelia; Thompson, John A. (Frontiers in Neurology, 2020)
Electrical stimulation mapping (ESM) using stereoelectroencephalography (SEEG) is an essential component in the work-up of surgical epilepsy. Since the initial application of ESM in the mid-1960s, it remains unparalleled in defining eloquent brain areas and delimiting seizure foci for the purposes of surgical planning. Here we briefly review the current state of SEEG stimulation, with a focus on techniques used for identifying the epileptogenic zone and eloquent cortex. We also summarize clinical data on the efficacy of SEEG stimulation in surgical outcomes and functional mapping. Finally, we briefly highlight future applications of SEEG ESM, including novel functional mapping approaches, identifying rare seizure semiologies, neurophysiologic investigations for understanding cognitive function, and its role in SEEG-guided radiofrequency thermal coagulation.